Towards interface design for virtual database / Zanariah Idrus...[et al.] - Idrus, Zanariah; Abdul Talib, Noor Hasnita; Zainal Abidin, Siti Zaleha; Omar, Nasiroh; Idrus, Zainura (Universiti Teknologi MARA, Kedah, 2019)
Today, big data has become as one of the important contribution in database management. It led to innovative ways of storing and organizing data which include structured and unstructured data. The unstructured data such as in news, reports, chats and surveys are basically loaded with heavy text data and numerous format. Thus, these data become challenging to be used for diverse purpose and are not appropriate to be stored in database. However, virtual database method has the capability to organize the unstructured data, and reconstruct into firm and concrete data. This approach carry out two major processes in databases which are mining and managing the data. However, the main problem is the insufficient support between people using databases and the heap of data collection. This is due to unawareness of clustered data organization as information is stored implicitly. Thus, this paper presents the conception of clustered data using the interface design model. Alignment of features and connections between the interface and knowledge composition allow users to access knowledge proficiently.